Comprehensive Physiology 1992
DOI: 10.1002/cphy.cp080235
|View full text |Cite
|
Sign up to set email alerts
|

Renal Prostaglandins and Other Eicosanoids

Abstract: The sections in this article are: Biochemistry Eicosanoid Synthesis Eicosanoid Degradation Lipoxygenase and Epoxygenase Derivatives of Arachidonic Acid Sites of Renal Eicosanoid Synthesis Mechanism of Peptide Hormone Stimulation of Eicosanoid Synthesis Eicosanoid R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 371 publications
3
24
0
Order By: Relevance
“…Most of the reported data indicated that renal PG, especially PGE2, are natriuretic, depending on their inhibitory action on NaCl transport in the ascending limb of Henle's loop and medullary collecting duct; they can also inhibit transport and increase renal excretion indirectly, secondary to intrarenal vasodilatation [11,12,20]. However, when PG were not given systemically but directly into renal tissue, using porous matrix cylinders placed in the cortico-medullary border area, antinatriuresis and an inhibition of proximal reabsorption were reported, apparently mediated by increased generation of angiotensin II and consequent stimulation of the proximal transport [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the reported data indicated that renal PG, especially PGE2, are natriuretic, depending on their inhibitory action on NaCl transport in the ascending limb of Henle's loop and medullary collecting duct; they can also inhibit transport and increase renal excretion indirectly, secondary to intrarenal vasodilatation [11,12,20]. However, when PG were not given systemically but directly into renal tissue, using porous matrix cylinders placed in the cortico-medullary border area, antinatriuresis and an inhibition of proximal reabsorption were reported, apparently mediated by increased generation of angiotensin II and consequent stimulation of the proximal transport [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, when PG were not given systemically but directly into renal tissue, using porous matrix cylinders placed in the cortico-medullary border area, antinatriuresis and an inhibition of proximal reabsorption were reported, apparently mediated by increased generation of angiotensin II and consequent stimulation of the proximal transport [21,22]. Elimination of endogenous PG by administration of inhibitors, such as indomethacin, has usually led to moderate antidiuresis, whereas the effect on U Na V was not uniform: a decrease or no change were most often reported [11]. As an exception, in two early studies natriuresis was reported in conscious dogs [23] and in humans [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1950s, many autocrines or paracrines have been reported to participate in the renal medullary adaptation to low P O 2 such as prostaglandin E 2 (PG E 2 ), adenosine (Ado), and nitric oxide (NO) (Brezis et al. 1991, Conrad & Dunn 1992, Roman & Zou 1993, Zou & Cowley 1997, Zou et al. 1999).…”
Section: Actions Of Autocrines and Paracrinesmentioning
confidence: 99%
“…As have demonstrated in other organs or tissues, the renal medulla has naturally developed various adaptive mechanisms to protect the cells from ischaemic and hypoxic injury in face of low P O 2 (Brezis et al. 1991, 1994, Conrad & Dunn 1992, Epstein 1997). Recently, there is accumulating evidence indicating that hypoxia‐induced molecular adaptation in mammalian tissues or cells is associated with the molecular regulation of gene expression and functional activity of oxygen‐sensitive gene products and this molecular adaptation is importantly attributed to local redox status.…”
mentioning
confidence: 99%